Ubiquitous Intelligence and Computing 8th International Conference, UIC 2011, Banff, Canada, September 2-4, 2011. Proceedings - Hsu, Ching-Hsien.; Yang, Laurence T.; Ma, Jianhua; Zhu, Chunsheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Ubiquitous Intelligence and Computing, UIC 2010, held in Banff, Canada, September 2011. The 44 papers presented together with two keynote speeches were carefully reviewed and selected from numerous submissions. The papers address all current issues in smart systems and services, smart objects and environments, cloud and services computing, security, privacy and trustworthy, P2P, WSN and ad hoc networks, and ubiquitous intelligent algorithms and applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computers and Society; Software Engineering; Personal Computing